Length–weight relationships of four small indigenous fish species from an inland artisanal fishery, Bangladesh. (10th April 2017) - Islam, M. A.; Siddik, M. A. B.; Hanif, M. A.; Chaklader, M. R.; Nahar, A.; Ilham, I.
Summary: This study reports the length–weight relationships (LWRs) of four small indigenous species, Trichogaster lalius (Hamilton, 1822), Nandus meni (Hossain & Sarker, 2013), Lepidocephalichthys annandalei (Chaudhuri, 1912) and Botia dario (Hamilton, 1822) collected between July 2015 and August 2016 from fishermen's catches landed in an inland fish landing center, northeastern Bangladesh. In the study, a new maximum total length (TL) is given for L. annandalei and LWRs of three species T. lalius, N. meni and L. annandalei for the first time in FishBase. Estimated LWRs were W  = .014 TL 3.17, ( r 2  = .982) for T. lalius, W  = .006 TL 3.38, ( r 2  = .961) for N. meni, W  = .004 TL 3.27, ( r 2  = .965) for L. annandalei and W  = .020 TL 2.87, ( r 2  = .978) for B. dario .